INFLUENCE OF INTERNAL ORGANIZATION ALENVIRONMENT ON PERFORMANCE OF COMMUNITY-BASED HIV AND AIDS ORGANIZATIONS IN NAIROBI COUNTY - Kinyua-Njuguna, Jane W.; Munyoki, Justus; Kibera, Francis (European Scientific Journal, ESJ, 2014)
Organizational performance is a key concern for stakeholders in both the profit and non-profit sectors. However, more attention has been focused on profit-making organizations with little emphasis on performance of community-based organizations (CBOs) and other Civil Society Organizations (CSOs) especially those located in sub-Saharan Africa. Theoretically, scholars in management discipline indicate that the internal environment of an organization influences its performance. Thus, performance is dependent on the internal structures and systems existing within an organization. This paper examines the impact of the internal organizational environment on performance of community-based HIV and AIDS organizations in Nairobi County, Kenya. The authors empirically assess the predicted relationship using survey data from 163 Community Based HIV and AIDS Organizations, in Nairobi County, Kenya. The study findings indicate that the internal environment of an organization has an impact on an organization’s effectiveness, efficiency, relevance and financial viability with impacts on the efficiency and relevance performance indicators. This study has important implications for managers of CBOs on the relevance of developing sustainable internal systems and structures within their organizations to enhance performance.